'Teabacco': Smoking of nicotine‐infused tea as an unintended consequence of prison smoking bans. (26th July 2018) - Puljević, Cheneal; Coomber, Ross; Kinner, Stuart A.; de Andrade, Dominique; Mitchell, Courtney; White, Alan; Cresswell, Sarah L.; Bowman, Jasper
Abstract: Introduction and Aims: Following the introduction of smoke‐free policies in prisons in several countries, there have been anecdotal reports of prisoners creating cigarettes by mixing nicotine patches or lozenges with tea leaves ('teabacco'). Among a sample of people recently released from smoke‐free prisons in Queensland, Australia, the aims of this study were to explore the perceived popularity of teabacco use, motivations for its use and describe the process of creating teabacco to identify potential associated health risks. Design and Methods: This study used a mixed‐methods design. Eighty‐two people recently released from prison in Queensland, Australia completed surveys at parole offices measuring teabacco use while incarcerated. Twenty‐one teabacco smokers took part in follow‐up, qualitative interviews to explore survey responses in greater depth. Results: The majority of survey participants (57%) reported smoking teabacco while incarcerated, with 37% smoking teabacco frequently (> once per week). Teabacco use was primarily motivated by cigarette cravings. Participants described the perceived inevitability of prisoners finding substitutes for tobacco. Multivariate analyses found that self‐rated poor physical health, having been incarcerated five or more times, experiencing cigarette cravings while incarcerated, and use of illicit drugs while incarcerated were positively associated with frequent teabacco use in prison. Discussion and Conclusions: Our findings suggest that teabacco use has become common practice in Queensland's smoke‐free prisons. Correctional smoking bans are an important public health initiative but should be complemented with demand and harm reduction measures cognisant of the risk environment.